2018
DOI: 10.1038/s41529-018-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alkali on the passivation of silicate glass

Abstract: Amorphous silica-rich surface layers, also called gels, can passivate silicate glass and minerals depending on environmental conditions. However, several uncertainties remain on the mechanisms controlling the formation of these layers. In this paper, the influence of exogenous ions supplied by solutions is studied, both on the formation and on the properties of the gel formed on international simple glass (ISG). ISG was altered at 90°C, pH 90°C 7, in silica-saturated solutions containing various alkaline catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…19,43,54 Recent studies have shown that the alteration layer undergoes major reorganization owing to the high reactivity of the silicate network. [53][54][55] It results in the formation of a microporous, hydrated, amorphous material with a large majority of non-connected pores, strongly reducing water diffusion. Moreover, as the alteration layer is an evolving material undergoing pore ripening, due to incessant hydrolysis and condensation of siloxane bonds, 54 transport of aqueous species through the growing layer becomes rate-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…19,43,54 Recent studies have shown that the alteration layer undergoes major reorganization owing to the high reactivity of the silicate network. [53][54][55] It results in the formation of a microporous, hydrated, amorphous material with a large majority of non-connected pores, strongly reducing water diffusion. Moreover, as the alteration layer is an evolving material undergoing pore ripening, due to incessant hydrolysis and condensation of siloxane bonds, 54 transport of aqueous species through the growing layer becomes rate-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Among the network formers, Si is the most abundant in typical silicate glasses and expected to be stable because the initial solution is saturated with the soluble silica species. 1,10,20,21 The Zr species is considered to be practically insoluble because the solubility product constant (K sp ) of its hydroxide is extremely small. The B species is easily dissolved.…”
mentioning
confidence: 99%
“…In either case, as the hydration front progresses and the pH in the hydrated layer increases due to the generation of free alkali, the silicate network of the glass deteriorates into a gel layer. The alteration gel layer exhibits an increased porosity resulting in cracking induced by tension between the unaltered and hydrated phases and in eventual dissolution of the glass as hydrolysis of the silica network progresses. Glass deterioration manifests visually in historical collections under two broad categories: microcracking, often called crizzling, ranging from thin, parallel lines to extended cracking, and weeping or sweating due to the presence of small liquid droplets on a glass surface or a thin, continuous surface film .…”
Section: Introductionmentioning
confidence: 99%